HDR 192Ir source speed measurements using a high speed video camera. Issue 1 (30th December 2014) - Fonseca, Gabriel P.; Viana, Rodrigo S. S.; Podesta, Mark; Rubo, Rodrigo A.; de Sales, Camila P.; Reniers, Brigitte; Yoriyaz, Hélio; Verhaegen, Frank
Abstract : Purpose: The dose delivered with a HDR 192 Ir afterloader can be separated into a dwell component, and a transit component resulting from the source movement. The transit component is directly dependent on the source speed profile and it is the goal of this study to measure accurate source speed profiles. Methods: A high speed video camera was used to record the movement of a 192 Ir source (Nucletron, an Elekta company, Stockholm, Sweden) for interdwell distances of 0.25–5 cm with dwell times of 0.1, 1, and 2 s. Transit dose distributions were calculated using a Monte Carlo code simulating the source movement. Results: The source stops at each dwell position oscillating around the desired position for a duration up to (0.026 ± 0.005) s. The source speed profile shows variations between 0 and 81 cm/s with average speed of ∼33 cm/s for most of the interdwell distances. The source stops for up to (0.005 ± 0.001) s at nonprogrammed positions in between two programmed dwell positions. The dwell time correction applied by the manufacturer compensates the transit dose between the dwell positions leading to a maximum overdose of 41 mGy for the considered cases and assuming an air‐kerma strength of 48 000 U. The transit dose component is not uniformly distributed leading to over and underdoses, which is within 1.4% for commonly prescribed doses (3–10 Gy). Conclusions: The source maintains its speed even for the short interdwell distances. Dose variations due to the transit dose component are much lower than the prescribed treatment doses for brachytherapy, although transit dose component should be evaluated individually for clinical cases.